Development of a Supply Chain Policy for Financing Instruments System of Foreign Economic Activity - Andrey V. Koren; Valentina A. Vodopyanova; Artem A. Pustovarov (International Journal of Supply Chain Management, 2019)
Supply Chain Finance (SCF) is a relatively recent thinking in Supply Chain Management literature. In article the comparative characteristic of the main instruments of bank financing of foreign economic activity (foreign trade activities) reflecting specifics of each tool and the main criteria for selection of financing of a concrete type by subjects of foreign trade activities is given by considering the supply chain strategy. For this purpose the main instruments of financing of foreign trade activities are defined and also schemes of their functioning, subjects of the relations, advantages and shortcomings are considered. As the main instruments of financing of foreign trade activities such tools as the letter of credit, leasing, factoring and forfaiting are analyzed. On the basis of statistical data the current state of foreign economic activity is analyzed, the trends of development of economy influencing activity of subjects of foreign trade activities are revealed. The standard and legal aspect of functioning the credit-substitutive tools in Russia is considered, the current and potential changes capable to influence further development of bank financing of foreign trade activities are analyzed. The system assessment of instruments of financing of foreign trade activities in terms of nonspecific risks is carried out. The problems interfering full and effective use of such foreign trade activities tools as factoring and forfaiting are revealed. As a result of a research the problems interfering development of instruments of bank financing of foreign trade activities in Russia and also the reasons constraining introduction of separate foreign tools in the Russian financial market are revealed. Conclusions that additional stimulation of development of factoring has reasonable character as the greatest advantage to the participant of foreign trade activities is reflected in increase in a turn and the profit of the organization are received. At the same time forfaiting can become an alternative to the usual credit in the long term as would allow the client to receive all sum of shipment at once, to issue longer delay of payment.